Age structure of stranded Loggerhead Turtles (Caretta caretta) in Turkey. Issue 4 (2nd October 2021) - Şirin, Ayfer; Başkale, Eyup
Abstract : The Mediterranean coast of Turkey includes important nesting beaches and marine habitats for the Loggerhead Turtle ( Caretta caretta ). We studied the demographic structure of this population by applying the skeletochronological method on stranded individuals. The mean age of stranded turtles was 27.0±3.83 years for females (N=10) and 40.1±14.97 years for males (N=7). The age of first reproduction was 23 years with a curved carapace length (CCL) of 61 cm for females and 21 years with a 67.5 cm CCL for males. The oldest observed female was 34 years old with a 67.8 cm CCL, while the oldest male was 59 years old with a 77.0 cm CCL. Incidental capture in fishing gear (60%) and marine vessel collisions (24%) were determined as the main causes of stranding.